Targeted Magnetic Nanoparticles for Remote Magnetothermal Disruption of Amyloid‐β Aggregates. Issue 14 (19th August 2015) - Loynachan, Colleen N.; Romero, Gabriela; Christiansen, Michael G.; Chen, Ritchie; Ellison, Rachel; O'Malley, Tiernan T.; Froriep, Ulrich P.; Walsh, Dominic M.; Anikeeva, Polina
Abstract : Remotely triggered hysteretic heat dissipation by magnetic nanoparticles (MNPs) selectively attached to targeted proteins can be used to break up self‐assembled aggregates. This magnetothermal approach is applied to the amyloid‐β (Aβ) protein, which forms dense, insoluble plaques characteristic of Alzheimer's disease. Specific targeting of dilute MNPs to Aβ aggregates is confirmed via transmission electron microscopy (TEM) and is found to be consistent with a statistical model of MNP distribution on the Aβ substrates. MNP composition and size are selected to achieve efficient hysteretic power dissipation at physiologically safe alternating magnetic field (AMF) conditions. Dynamic light scattering, fluorescence spectroscopy, and TEM are used to characterize the morphology and size distribution of aggregates before and after exposure to AMF. A dramatic reduction in aggregate size from microns to tens of nanometers is observed, suggesting that exposure to an AMF effectively destabilizes Aβ deposits decorated with targeted MNPs. Experiments in primary hippocampal neuronal cultures indicate that the magnetothermal disruption of aggregates reduces Aβ cytotoxicity, which may enable future applications of this approach for studies of protein disaggregation in physiological environments. Abstract : Remotely triggered hysteretic heat dissipation by magnetic nanoparticles (MNPs) selectively targeted to amyloid‐β (Aβ) protein can be used to break up self‐assembled aggregates that are characteristic of Alzheimer's disease, causing a dramatic reduction in aggregate size from microns to tens of nanometers. Furthermore, the experiments in primary hippocampal neurons indicate neuroprotective effects of our approach against Aβ cytotoxicity.